DETERMINANT OF HEALTH PROTOCOL IMPLEMENTATION AMONG ELDERLY WITH CHRONIC DISEASE IN JEMBER - Dewi, Sofia Rhosma (Nurse and Holistic Care, 2021)
Background: Elderly is one of the vulnerable groups against COVID 19 infection. The mortality rate from COVID 19 is the highest in the elderly. The chronic disease is worsening the outcome. Objective: This study aimed to find the determinant of the implementation of health protocols among the elderly with chronic disease. Methods: This study was a correlational study conducted with a cross-sectional approach. A total of 437 elderly were selected through consecutive sampling techniques. The respondents were asked to fill the KAP questionnaire through a google form. The data were analysed using binary logistic regression and multivariate logistic regression techniques using SPSS. Result: The results showed that educational level (p-value 0,088); living arrangement (p-value 0,035); knowledge (p-value 0,026); occupation (p-value 0, 042) and the implementation of self-care management (p-value 0,047) were correlated with the implementation of health protocols among the elderly with chronic disease. Knowledge became the main determinant of the health protocol implementation among the elderly with OR 8,456 95%CI (3,495 – 20,455). Conclusion: It can be concluded that the elderly with adequate knowledge has the potential to be 8,4 times more likely to implement the health protocols properly. Health education about the appropriate implementation of health protocol needs to be carried out using a plain language that is easily accepted by the elderly